Using an analysis of concrete and cement epd: verification, selection, assessment, benchmarking and target setting - Lucie Schmitt; Jena Jeong; Jean-Marc Potier; Laurent Izoret; Jonathan Mai-Nhu; Nicolas Decousser; Thomas Pernin (Acta Polytechnica CTU Proceedings, 2022)
Carbonation of concretes is a natural physico-chemical process that can be described as a reaction between the carbon dioxide contained in the air and the cement matrix. Carbonation concerns all concretes types in contact with the ambient air but also concretes in ground, from production stage to use and end-of-life stages. The amount of carbon dioxide bound varies according to the type of binder, the compacity of concrete and the environmental conditions during the use and the end-of-life stages. To consider the re-carbonation of concrete, works have been carried out within the framework of the European standardization group CEN/TC229/WG5 and in CEN/TC104. A methodology to consider the re-carbonation of concrete structures has been proposed in the NF EN 16757 standard on environmental product declarations for concrete and concrete elements. In addition, FD CEN/TR 17310 provides detailed recommendations regarding carbonation and absorption of carbon dioxide in concrete and give some precisions for application of NF EN 16757. This is an important topic towards a sustainable development in the current context of circular economy and CO2 uptake related to the French energy labelling (E+C-). In this paper, numerical and analytical carbonation models are used to estimate the CO2 binding ability of concrete structures. The obtained results are compared to the methodology proposed in Appendix BB of NF EN 16757 standard. They confirm that the methodology described in the NF EN 16757 standard leads to estimated degree of carbonation of the same order of magnitude. The advantage of using more advanced models lies in a better consideration of environmental parameters, the possibility to simulate the behaviour of crushed concrete, its reuse in new concrete as recycled aggregate and the possibility to simulate the carbonation of concretes in ground. This is an immediate perspective in the ongoing work in the French national project FastCarb on accelerated carbonation of recycled concrete aggregates.